Transformasi Digital Dalam Administrasi Pertanahan: Analisis Yuridis Terhadap Sertipikat Tanah Elektronik - Deva Sakti Susmana (Riviera Publishing, 2025)
With the rapid development of digital technology, Indonesia faces challenges in the digital transformation of land administration. The implementation of electronic land certificates is expected to improve efficiency, transparency, and legal certainty. This study analyzes the role of electronic land certificates, the challenges in securing them, and the supporting policies. The research finds that electronic land certificates accelerate administration, reduce document falsification, and enhance transparency. However, significant challenges remain regarding digital infrastructure, digital literacy, and data security. Therefore, efforts are needed to accelerate infrastructure distribution, improve digital literacy, and strengthen regulations on personal data protection. This study also highlights the importance of personal data protection policies in the use of electronic land certificates. Strategic measures are necessary to ensure land data is secure and protected from cyber threats.